Multiple Connection Pattern Combination From Single-Mode Data for Mild Cognitive Impairment Identification - Li, Weikai; Xu, Xiaowen; Wang, Zhengxia; Peng, Liling; Wang, Peijun; Gao, Xin (Frontiers in Cell and Developmental Biology, 2021)
Mild cognitive impairment (MCI) is generally considered to be a key indicator for predicting the early progression of Alzheimer's disease (AD). Currently, the brain connection (BC) estimated by fMRI data has been validated to be an effective diagnostic biomarker for MCI. Existing studies mainly focused on the single connection pattern for the neuro-disease diagnosis. Thus, such approaches are commonly insufficient to reveal the underlying changes between groups of MCI patients and normal controls (NCs), thereby limiting their performance. In this context, the information associated with multiple patterns (e.g., functional connectivity or effective connectivity) from single-mode data are considered for the MCI diagnosis. In this paper, we provide a novel multiple connection pattern combination (MCPC) approach to combine different patterns based on the kernel combination trick to identify MCI from NCs. In particular, sixty-three MCI cases and sixty-four NC cases from the ADNI dataset are conducted for the validation of the proposed MCPC method. The proposed method achieves 87.40% classification accuracy and significantly outperforms methods that use a single pattern.